Relapse Tendency among Individuals with Substance Use: Exploring the influence of Family Dynamic and Drug Abstinence Self - Efficacy - Saleem, Adeeba; Masood, Sobia (Journal of Development and Social Sciences, 2024)
The study aimed to investigate the predictive role of family functioning and drug abstinence self-efficacy on relapse tendency, the intermediating role of drug abstinence self-efficacy between family functioning and relapse tendency, and the influence of demographic variables (age, drug use history, reasons for use, drug types, marital status, and employment status) on the study variables. The study highlights the relapse tendencies among individuals with substance use, focusing on the role of family dynamics and drug abstinence self-efficacy. It aims to understand how poor family functioning and low drug abstinence self-efficacy contribute to relapse. The research utilizes the Cognitive Social Learning Theory and Relapse Prevention Model to explore these influences. The research was quantitative, correlation study using a cross-sectional research design. Data was obtained from rehabilitation centres. The study found that poor family functioning and low drug abstinence self-efficacy significantly increase relapse tendencies among individuals with substance use disorders. Regression analysis revealed that family dynamics and self-efficacy are strong predictors of relapse, highlighting the need for family-inclusive interventions. These findings suggest that improving family support and enhancing self-efficacy can effectively reduce relapse rates, emphasizing the importance of comprehensive treatment plans. It is recommended to integrate family-based therapy and self-efficacy training into substance use treatment programs to effectively reduce relapse rates.